Impact of PaGLK transgenic poplar on microbial community and soil enzyme activity in rhizosphere soil - Zheng, Yu; Lv, Guan Bin; Chen, Kun; Yu, Qibin; Niu, Ben; Jiang, Jing; Liu, Guifeng (Frontiers in Bioengineering and Biotechnology, 2022)
Rhizosphere microorganisms are essential parts in maintaining soil ecological functions. Reforestation using genetically modified trees might have great potential to enhance tree production in biotic and abiotic stress, however, their long-term impact on rhizosphere microorganisms is scant. In this study, we studied soil enzyme activities and composition of rhizosphere microorganisms in 2-year-old transgenic PaGLK overexpression (OE), repressed expression (RE) and wild-type (WT) poplar (P. alba × P.berlinensis). The root exudates of PaGLK transgenic poplar (P.alba × P. berlinensis) were analyzed by liquid chromatography-mass spectrometry (LC-MS). The results showed that there were significant difference for soil sucrase, urease, catalase, neutral protease and cellulase between the transgenic and WT lines at different growth periods. Alpha diversity analysis showed that bacterial community abundance and diversity for RE lines were significantly lower than WT (P < 0.05), while RE lines for fungi were significantly higher than WT lines. At the genus level, Burkholderia was the dominant group of rhizosphere bacterial community, and the relative abundance for RE was significantly higher than WT. Tomentella was the dominant group for fungi community. Serendipita for RE was significantly higher than WT and OE. Main metabolite contents of (S)-ACPA, geniposidic acid, agnuside, hydroquinone and pyranocoumarins were significantly different among transgenic lines. These results suggest that transgenic activities have effects on root exudates, rhizosphere soil enzyme activities and soil microbial community composition, but long term effects need to be further investigated.